Pengaruh Inovasi Produk dan Brand Ambassador EXO Terhadap Keputusan Pembelian: Studi Kasus Terhadap Konsumen Scarlett Whitening di Tangerang Selatan - Novita Ramadayanti (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2024)
This study aims to analyze the influence of product innovation and brand ambassador to purchasing decisions Scarlett Whitening body lotion tube products in South Tangerang. Scarlett Whitening, a local Indonesian beauty brand, is known for a variety of skin care products such as body lotions, scrubs, scrubs, serums, and creams that aim to brighten and maintain healthy skin. With the motto" Reveal your Beauty, " Scarlett has managed to increase the confidence of its users. This study uses Partial Least Square (PLS) method with the help of SmartPLS and quantitative approach through google form questionnaire survey. The sample consisted of 60 respondents who had bought Scarlett tube body lotion products and knew the boy band EXO. The results showed that product innovation has a significant influence on purchasing decisions with a statistical t-value of 2.263 ≥ 1,96 and p-value of 0.000 ≤ 0,05. In addition, brand ambassadors also have a significant influence on purchasing decisions with a statistical t-value of 3.123 ≥ 1,96 and p-value of 0.000 ≤ 0,05.